Sekala Brak Kingdom: The Forerunner of Lampung Civilisation 4 Kepaksian Skala Berak - Muhammad, Ulul Azmi; Sandi, Galuh; Amala, Istiqomah Ahsanu; Nugraha, Rio Eka (Swarnadwipa, 2024)
This research discusses the role of Sekala Brak Kingdom in shaping the cultural identity of Lampung people through the Four Kepaksian system (Pernong, Belunguh, Nyerupa, and Bejalan Di Way). Using a qualitative approach, data was obtained through in-depth interviews, participatory observation, and documentation. The results showed that customary values such as Piil Pesenggiri (self-esteem), Nemu Nyimah (hospitality), Sakai Sambayan (mutual cooperation), and Bejuluk Beadek (respect for identity) remain relevant in people's lives. However, the challenges of modernisation and the lack of regeneration of traditional leaders threaten the sustainability of these traditions. Preservation strategies such as multicultural education and the development of culture-based tourism are proposed to maintain the heritage values of the Sekala Brak Kingdom. This research confirms the importance of maintaining social harmony and local culture in the midst of globalisation.